Monday

March 2, 2015

March 2, 2015

Posted by **Christine** on Wednesday, May 7, 2008 at 11:09am.

y' + (y)tanh(x) - 2e^x = 0

- calculus -
**Count Iblis**, Wednesday, May 7, 2008 at 2:00pmFirst solve the homogeneous equation:

y' + (y)tanh(x)= 0

Replace the integration constant by an unknown function and substitute that back in the Diff. equation:

y' + (y)tanh(x) - 2e^x = 0

then solve for that unknown function.

**Answer this Question**

**Related Questions**

Calculus - Solve the differential equation dy/dx = -xe^y and determine the ...

PLEEEEEAAAASE HELP WITH DIFFERENTIAL EQ PROBLEMS!! - 1) What are the equilibrium...

calculus - Solve the following differential equation: f"(x)=sinx, x(0)=0, x'(0)=...

Calculus - Which of the following is a separable, first-order differential ...

calculus-differential equation - Consider the differential equation: (du/dt)=-u^...

Differential Equations - Solve the seperable differential equation for U. du/dt...

Calculus - Solve the seperable differential equation 8yy =x. Use the following...

Help with differential eqs problem???? (Calculus) - Consider the differential ...

CALCULUS - Using the separation of variables technique, solve the following ...

Calculus AB - Solve the differential equation: dy/dx= (x^2+y^2)/(2xy) I know how...